World education patterns in the global north : the ebb of global forces and the flow of contextual imperatives - Wolhuter, C. C.; Wiseman, Alexander W. (International perspectives on education and society, 2022)
Comparative and International Education is a dynamic and growing field facing extraordinary challenges in every corner of the world. World Education Patterns in the Global North surveys the educational responses and new educational landscapes being developed as a consequence of powerful global forces demanding change within the Global North's educational contexts, including North America, Central and South-East Europe, and East Asia, These forces include the ecological crisis, the population explosion, the changing nature of work, the rise of knowledge economies, economic internationalism, the Fourth Industrial Revolution, the technology revolution, changing social relations, the empowerment of minority interest groups, the rise of multicultural societies, the diminishing stature of the nation-state, and the rise of supra-national and international political structures.